ANALISIS DETERMINAN TINGKAT PARTISIPASI PETANI DALAM IMPLEMENTASI GOOD AGRICULTURAL PRACTICES (GAP) PADI ORGANIK: STUDI KASUS PADA KELOMPOK TANI PANGUDI BOGO, KABUPATEN BOYOLALI - Damayanti, Adhisty Puri; Suswadi, Suswadi; Arbianti, Arbianti; Arum, Mutiarra Ridyo; Permatasari, Dewi Rahmawati Intan (Universitas Islam Kadiri, 2025)
Organic rice cultivation following Standard Operating Procedures (SOPs) is a key strategy for sustainable agriculture, yet its success depends on farmers’ participation in implementing Good Agricultural Practices (GAP). This study analyzes the factors influencing farmers’ participation in GAP within the Pangudi Bogo Farmers’ Group, Boyolali Regency. Using a quantitative approach with 30 respondents, data were analyzed by descriptive statistics and Ordinary Least Squares (OLS) method through multiple linear regression to identify factors affecting farmers’ participation in GAP. Farmers’ participation in GAP implementation was found to be relatively high. The results indicate that experience in organic farming and extension have a significant positive effect on farmers’ participation, whereas farmer satisfaction has a significant negative effect. In contrast, conventional farming experience and farm size were found to have no significant effect. The findings of this study highlight that enhancing organic farming experience and the role of agricultural extension agents are key factors in strengthening farmers’ participation in GAP. Moreover, farmers’ satisfaction with cultivation outcomes should be directed as a motivation to further engage in GAP implementation.